Prevalence of Pre-eruptive Intra-Coronal Resorption in Pediatric Population: A Retrospective Analysis - Irem Mergen Gultekin; Pınar Serdar Eymirli; Sevilay Karahan (Association of Support to Oral Health Research (APESB), 2024)
Objective: To evaluate the prevalence of pre-eruptive intra-coronal resorption (PEIR) lesions in the pediatric population. Material and Methods: 8341 impacted teeth were evaluated regarding PEIR lesions via panoramic radiographs of 968 patients aged 2-18 who applied between 2021 and 2022. The number of affected teeth, the number of the tooth, the degree of the lesion, the location of the defect, and the presence of ectopic position were recorded. PEIR lesions are categorized based on the thickness of the affected dentin: Grade 1 (less than 1/3), Grade 2 (between 1/3 and 2/3), and Grade 3 (more than 2/3). All analyses were performed with IBM SPSS 23.0, and p value 0.05 was considered significant. Results: The number of teeth with PEIR defects was 71 (0.86%), while the number of patients with PEIR defects was 58 (5.99%). Mandibular premolars (42.3%) are the most commonly defective teeth, followed by mandibular molars (39.5%). The majority of defects were classified as Grade 1. In patients with Grade 3 lesions, no more than one defect was observed. There was a significant relationship between the degree of the defect and the number of defects observed. Conclusion: Detecting defective teeth in pediatric patients' control radiographs is critical for early treatment. This study emphasized that the prevalence of defective teeth is high in pediatric patients, and pediatric dentists should be cautious about these defects.